PERBANDINGAN KINERJA INDEKS PAPAN UTAMA DENGAN INDEKS PAPAN PENGEMBANGANDI BURSA EFEK INDONESIA - Dita Rahmawati; Nadia Asandimitra (Universitas Trunojoyo Madura, 2016)
This study aims to identify and analyze differences performance of Main Board Index (MBX) and Development Board Index (DBX) using a portfolio performance measurement model Risk Adjusted Performance in 2010-2014. Issuers listed on the Indonesia Stock Exchange was divided into two boards, namely MBX and DBX, where the placement of issuers and emiten who approved the recording based on the placement requirements on each board recording. The test results using Mann-Whitney test showed the difference in stock index performance between MBX andDBX using 3 methods of performance measurement. Main board has a higher risk on average than Development Board, and resulting a higher return. This is contrary to the theory of market anomalies size effect which says that small sized companies deliver greater return compared with return provided by the big cap. Such as the investments principle of high risk high return, if investors want a high return then will be faced with a high risk anyway. Thus, to get the maximum return, it is better to invest in the shares of Main Board.